A polypropylene composite material and preparation method thereof

By using silane-modified nanocellulose and synthetic mica powder in polypropylene composite materials, a self-built barrier network is formed, which solves the problem of insufficient solvent swelling resistance of existing polypropylene materials, and achieves efficient solvent barriers and Excellent component dispersion and appearance.

CN117264325BActive Publication Date: 2025-02-18JIANGSU KINGFA SCI & TECH ADVANCED MATERIALS CO LTD

Patent Information

Application Number
CN202311430855.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-02-18
Estimated Expiration
2043-10-31

AI Technical Summary

Technical Problem

The existing polypropylene materials have insufficient solvent swelling resistance when they come into contact with organic solvents such as engine oil. Especially in the field of engineering vehicles, solvent resistance is difficult to meet the requirements of more than 200 hours. At the same time, the introduction of modifiers will lead to reduced component dispersion and appearance problems.

Method used

By introducing silane-modified nanocellulose and synthetic mica powder into the polypropylene composite material, a self-built barrier network is formed to improve the material's solvent swelling resistance and component dispersion.

Benefits of technology

The solvent swelling resistance of the polypropylene composite material is significantly improved, and it can effectively block the penetration and migration of solvents within a time of more than 200 hours, while maintaining excellent component dispersion and good appearance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004523597730000081
    Figure BDA0004523597730000081
  • Figure BDA0004523597730000082
    Figure BDA0004523597730000082
  • Figure BDA0004523597730000092
    Figure BDA0004523597730000092
Patent Text Reader

Abstract

The invention discloses a polypropylene composite material and a preparation method thereof, belonging to the technical field of polymer materials. The product can greatly improve the solvent swelling resistance of the product through the synergistic effect of the combination of specific silane-modified nanocellulose and synthetic mica powder. At the same time, the product has excellent component dispersibility, the appearance will not be affected, and there is no obvious pitting or flow mark on the surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a polypropylene composite material and a preparation method thereof. Background Art

[0002] In the automotive industry, some parts such as instrument panels, exterior bumpers, and housing protective covers are made of plastic, among which polypropylene is the most frequently used material.

[0003] However, since automotive parts are exposed to organic reagents such as engine oil for a long time, the polypropylene material used to make the parts is required to have a certain solvent swelling resistance. But with the functionalization and universal use of automotive products, the swelling resistance of existing polypropylene materials is gradually unable to meet market demand, especially in some engineering vehicle fields, where the solvent resistance requirements for automotive parts have reached more than 200 hours.

[0004] In the prior art, the solution to improve the solvent resistance of polypropylene materials is generally to introduce some solvent stabilizers into the product, so as to control the matrix resin and inhibit its penetration after contact with the solvent. However, the current solvent swelling resistance of such products is still poor. At the same time, the introduction of these modifiers will lead to a decrease in the dispersibility of the overall components, which will ultimately greatly affect the appearance of the product and greatly limit its scope of use. Summary of the invention

[0005] Based on the defects of the prior art, the purpose of the present invention is to provide a polypropylene composite material. The product can greatly improve the solvent swelling resistance of the product through the synergistic effect of the combination of specific silane-modified nanocellulose and synthetic mica powder. At the same time, the product has excellent component dispersion, the appearance will not be affected, and there are no obvious pitting or flow marks on the surface.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A polypropylene composite material comprises the following components in parts by weight:

[0008] 50-90 parts of polypropylene resin, 3-15 parts of toughening agent, 5-25 parts of talc, 1-2 parts of silane-modified nanocellulose, 2-5 parts of synthetic mica powder and 0.1-2.5 parts of processing aid.

[0009] Preferably, the polypropylene composite material comprises the following components in parts by weight:

[0010] 60-80 parts of polypropylene resin, 5-10 parts of toughening agent, 10-20 parts of talc, 1-2 parts of silane-modified nanocellulose, 2-5 parts of synthetic mica powder and 0.1-2.5 parts of processing aid.

[0011] Preferably, in the polypropylene composite material, the mass percentage of the polypropylene resin is not less than 60wt%.

[0012] Existing polypropylene composite materials usually reduce the elastomer component with high oil absorption to improve the solvent swelling resistance of the product, but this approach will reduce the comprehensive performance of the product, and ultimately affect the function of the product. In order to overcome the defects of existing products, the polypropylene composite material of the present invention uses cellulose, a nano-molecular polysaccharide, and synthetic mica powder as a key component. Based on the silane groups loaded on the surface after silane modification, nanocellulose can be easily combined with synthetic mica powder, and automatically form a lamellar overlapping barrier network on the surface of the matrix polypropylene resin. This self-built network not only has good compatibility among product components, does not affect the dispersion of product components, and has a good appearance of the product, but also has good stability. When the product comes into contact with a solvent, it can effectively block the penetration and migration of the solvent for a long time, so that the solvent swelling resistance of the product is greatly improved.

[0013] On the other hand, due to the lamellar structure of synthetic mica powder itself, the size of cellulose must reach the nanometer level in order to be effectively dispersed in the gaps between the mica powder. After experiments, the inventors found that when the cellulose in the product is only at the micron level, it is difficult for the product to achieve solvent swelling resistance. At the same time, unlike natural mica powder, synthetic mica powder itself has higher hardness and toughness, so it has good structural stability and will not damage the lamellar structure due to the product processing process. If synthetic mica powder is replaced with natural mica powder, the same technical effect cannot be achieved.

[0014] Preferably, the synthetic mica powder is fluorphlogopite powder with a melting point of 1370-1380°C.

[0015] Preferably, the mass ratio of the silane-modified nanocellulose to the synthetic mica powder is (1:2) to (2:5).

[0016] In the polypropylene composite material of the present invention, compared with the polypropylene resin and talc powder as a filler, the added amount of silane-modified nanocellulose and synthetic mica powder is less. The main reason is that excessive addition of the two will also cause appearance problems of the product. When the total amount of the two added is certain, it is found through screening that the comprehensive performance of the mass ratio of the two within the above range is better.

[0017] Preferably, the diameter of the silane-modified nanocellulose is 2 to 80 nm, accounting for more than 95%, and the length is 30 to 2000 nm, accounting for more than 95%;

[0018] More preferably, the diameter of the silane-modified nanocellulose is 10 to 30 nm, accounting for more than 95%, and the length is 100 to 500 nm, accounting for more than 95%.

[0019] The diameter and length of the silane-modified nanocellulose are detected by a particle size detector.

[0020] In the present invention, the diameter and length range of the silane-modified nanocellulose is limited to more than 95% of the entire material, and if the materials in other ranges of diameter and length are ignored by those skilled in the art, it can be considered that the range of diameter and length is the range of the entire silane-modified nanocellulose.

[0021] In the polypropylene composite material described in the present invention, the main function of the silane-modified nanocellulose is to act as a binder and gap filler for the mica sheets in the self-built barrier network. Therefore, there are certain differences in the application effects of silane-modified nanocellulose of different sizes. After screening, when the types within the above preferred range are used as product components, the product has better resistance to solvent swelling.

[0022] Preferably, the silicon content of the silane-modified nanocellulose is 10 to 12 ppm by mass.

[0023] The silicon mass content of the silane-modified nanocellulose is obtained by IPC detection.

[0024] More preferably, the silane-modified nanocellulose is obtained by mixing and dispersing nanocellulose and a silane coupling agent.

[0025] More preferably, the mass ratio of the silane coupling agent to the nanocellulose in the silane-modified nanocellulose is (0.5-1.5):100.

[0026] More preferably, the silane coupling agent includes at least one of γ-aminopropyl triethoxysilane siloxane, γ-glycidyloxypropyl trimethoxysilane, and γ-methacryloxypropyl siloxane.

[0027] The inventors have found through experiments that, since nanocellulose itself has abundant surface groups, modification with various types of silane coupling agents commonly used can effectively achieve its compatibility in polypropylene matrix resin.

[0028] Preferably, the average flake diameter of the synthetic mica powder is 20 to 80 μm.

[0029] More preferably, the average flake diameter of the synthetic mica powder is 30 to 60 μm.

[0030] More preferably, the average flake diameter of the synthetic mica powder is in the range of one or any two of 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, and 60 μm.

[0031] The flake diameter of the synthetic mica powder is obtained by testing with a particle size tester.

[0032] As mentioned above, the synthetic mica powder in the technical solution of the present invention is a key component for forming a barrier structure, but the flake diameter of this component is not necessarily the larger the better. Experiments have shown that when the flake diameter of the synthetic mica powder is preferably in the range of 30 to 60 μm, the comprehensive performance of the product is better.

[0033] Preferably, the polypropylene resin is copolymerized polypropylene.

[0034] More preferably, the copolymerized polypropylene resin has a melt flow rate of 1 to 100 g / 10 min at 230° C. and a load of 2.16 kg according to ISO 1133-2011.

[0035] More preferably, the copolymerized polypropylene resin has a melt flow rate of 10 to 50 g / 10 min at 230° C. and a load of 2.16 kg according to ISO 1133-2011.

[0036] More preferably, the copolymerized polypropylene resin has a melt flow rate of 10 g / 10 min, 15 g / 10 min, 20 g / 10 min, 25 g / 10 min, 30 g / 10 min, 35 g / 10 min, 40 g / 10 min, 45 g / 10 min, 50 g / 10 min or any two of the range values ​​at 230 ° C and 2.16 kg load according to ISO 1133-2011.

[0037] Preferably, the mesh size of the talc is ≥1000 mesh.

[0038] Preferably, the mesh size of the talc is one or any two of 1000 mesh, 1250 mesh, 2000 mesh, 3000 mesh, 3500 mesh, 4000 mesh, 5000 mesh, 6000 mesh, 7000 mesh and 8000 mesh.

[0039] More preferably, the mesh size of the talc is 1250 to 3500 mesh.

[0040] In the polypropylene composite material described in the present invention, talcum powder acts as the main filler, but it itself will also be brought into the self-built isolation protection network layer formed by the product. Therefore, when the mesh number of talcum powder is ≥1000 mesh and the particle size is small, it can effectively assist silane-modified nanocellulose to better fill the gaps in the isolation network, thereby making its isolation effect against solvents better.

[0041] In addition, the inventors have experimentally verified that each talcum powder can use existing commercial brands as raw materials to prepare products based on actual usage needs, or it can purchase a commercial product in advance and then use it after particle screening. For talcum powder of the same mesh size, the inventors have compared that the performance of products prepared from talcum powder of different models or sources is basically the same, indicating that in the product system described in the present invention, the properties of talcum powder other than mesh size have no effect on the performance of the product concerned by the present invention.

[0042] Preferably, the toughening agent is at least one of ethylene / octene copolymer, ethylene / butene copolymer and ethylene / propylene copolymer.

[0043] More preferably, the toughening agent has a melt index of 1 to 20 g / 10 min at 230° C. and a load of 2.16 kg according to ISO 1133-2011.

[0044] Preferably, the processing aid includes at least one of an antioxidant and a lubricant.

[0045] More preferably, the antioxidant is at least one of a hindered phenol antioxidant and a phosphite antioxidant.

[0046] More preferably, the antioxidant is a mixture of a hindered phenol antioxidant and a phosphite antioxidant in a ratio of (0.8-1.2):(0.8-1.2).

[0047] More preferably, the lubricant is at least one of a silicone lubricant and a wax lubricant.

[0048] Based on the needs of actual products, those skilled in the art can appropriately introduce some components commonly introduced into polypropylene composite products without affecting the performance of the product, such as antioxidants to improve the aging resistance of the product, lubricants to improve the processing performance of the product, etc. Furthermore, components such as dispersants to improve the processing dispersibility of the product can also be introduced, and the dispersant can be at least one of polyol esters and fatty alcohol esters.

[0049] Another object of the present invention is to provide a method for preparing the polypropylene composite material, comprising the following steps:

[0050] After the components are uniformly mixed, they are melt-extruded and granulated in a twin-screw extruder to obtain the swelling-resistant polypropylene composite material.

[0051] The preparation method of the polypropylene composite material of the present invention has simple operation steps and can realize industrial scale production.

[0052] Preferably, the temperature range of the twin-screw extruder is set to: 160-240° C., and the screw speed is 400-600 r / min.

[0053] Another object of the present invention is to provide application of the polypropylene composite material in the preparation of automobile parts.

[0054] Preferably, the automotive component comprises a separator panel.

[0055] The polypropylene composite material of the present invention is based on a specific self-built isolation network. When applied to automotive parts, it can effectively block the corrosion of parts by organic solvents such as engine oil. The efficiency of penetration and precipitation of organic solvents in the product is extremely low, and the precipitation time can be more than 200 hours. At the same time, the appearance is good without obvious defects.

[0056] The beneficial effect of the present invention is that the present invention provides a polypropylene composite material and a preparation method thereof. The product can greatly improve the solvent swelling resistance of the product through the synergistic effect of the combination of specific silane-modified nanocellulose and synthetic mica powder. At the same time, the component dispersion of the product is excellent, the appearance will not be affected, and there are no obvious pitting or flow marks on the surface. DETAILED DESCRIPTION

[0057] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.

[0058] It should be noted that the synthetic mica used in the specific implementation manner of the present technical solution is fluorophlogopite with a melting point of 1370-1380°C, while the main components of the natural mica used are muscovite and phlogopite with a melting point of ≤900°C. It is well known to those skilled in the art that the two are not limited by the literal descriptions of "synthetic" and "natural", and the differences are not elaborated here one by one.

[0059] Examples 1 to 16

[0060] An embodiment of a polypropylene composite material and application thereof according to the present invention, the components of the polypropylene composite material are shown in Table 1.

[0061] The preparation method of the polypropylene composite material comprises the following steps:

[0062] All the components in the formula are mixed uniformly in a high-speed mixer and then fed into a twin-screw extruder from a main feeding port for melt blending, extrusion and granulation to obtain the polypropylene composite material.

[0063] When the components are melt-blended and extruded, the temperature zones of the twin-screw extruder are set to 165-175°C for zone one, 185-195°C for zone two, 205-215°C for zone three, 205-215°C for zone four, 215-225°C for zone five, 215-225°C for zone six, 225-235°C for zone seven, 225-235°C for zone eight, and 225-235°C for zone nine, the screw speed is 500rpm, and the screw aspect ratio is 40:1.

[0064] Comparative Examples 1 to 9

[0065] The difference between the comparative examples and the embodiments is only in the types and proportions of components, as shown in Table 2.

[0066] Among the components described in each embodiment and comparative example,

[0067] The polypropylene resin 1 is M30RHC produced by Zhenhai Refining and Chemical, copolymerized polypropylene, and according to ISO 1133, the melt flow rate at 230°C and 2.16kg load is 26g / 10min;

[0068] The polypropylene resin 2 is Z30S produced by Zhenhai Refining and Chemical, a copolymer polypropylene, and according to ISO 1133, the melt flow rate at 230°C and 2.16kg load is 25g / 10min;

[0069] The toughening agent 1 is POE 7447 produced by Dow Chemical, an ethylene / octene copolymer, and has a melt index of 5 g / 10 min at 230° C. and a load of 2.16 kg according to ISO1133;

[0070] The toughening agent 2 is POE 7467 produced by Dow Chemical, an ethylene / butene copolymer, and has a melt index of 1.5 g / 10 min at 230° C. and a load of 2.16 kg according to ISO 1133;

[0071] The talcum powder 1 is TYT-777A, 3000 mesh talcum powder produced by Beihai Group;

[0072] The talcum powder 2 is TY90-7-C, 2000 mesh talcum powder produced by Guangxi Longwei;

[0073] The talcum powder 3 is Ultral5, 5000 mesh talcum powder produced by Coix seeds and Artemisia selengensis;

[0074] The talcum powder 4 is TYT-8875B produced by Beihai Group, 1000 mesh talcum powder;

[0075] The nanocellulose 1 is a product produced by Wuhan Kangqiong, with a diameter of 10-30nm accounting for more than 95%, and a length of 100-500nm accounting for more than 95%;

[0076] The nanocellulose 2 is a product produced by Wuhan Kangqiong, with a diameter of 2 to 10 nm accounting for more than 95%, and a length of 30 to 100 nm accounting for more than 95%;

[0077] The nanocellulose 3 is a product produced by Wuhan Kangqiong, with a diameter of 40-80nm accounting for more than 95%, and a length of 0.5-2um accounting for more than 95%;

[0078] The cellulose is produced by Wuhan Kemik, with a diameter of 0.2-0.5 μm accounting for more than 95% and a length of 2-5 μm accounting for more than 95%;

[0079] The silane coupling agent 1 is KH-550 produced by Nanjing Shuguang, γ-aminopropyl triethoxysiloxane.

[0080] The silane coupling agent 2 is KH570 produced by Nanjing Shuguang, γ-methacryloxypropyl siloxane.

[0081] The silane-modified nanocellulose 1 is homemade, and the homemade method is to mix the nanocellulose 1 and the silane coupling agent 1 at a mass ratio of 100:1 and stir for 2 minutes until uniform, and the silicon mass content is 10ppm;

[0082] The silane-modified nanocellulose 2 is homemade, and the homemade method is to mix the nanocellulose 2 and the silane coupling agent 1 at a mass ratio of 100:1 and stir for 2 minutes until uniform, and the silicon mass content is 11ppm;

[0083] The silane-modified nanocellulose 3 is homemade, and the homemade method is to mix the nanocellulose 3 and the silane coupling agent 1 at a mass ratio of 100:1 and stir for 2 minutes until uniform, and the silicon mass content is 11ppm;

[0084] The silane-modified nanocellulose 4 is homemade, and the homemade method is to mix the nanocellulose 1 and the silane coupling agent 2 at a mass ratio of 100:1 and stir for 2 minutes until uniform, and the silicon mass content is 12ppm;

[0085] The silane-modified cellulose is homemade, and the homemade method is to mix cellulose and silane coupling agent 1 at a mass ratio of 100:1 and stir for 2 minutes until uniform, and the silicon mass content is 10ppm;

[0086] The silane-modified talc powder is homemade, and the homemade method is to mix the talc powder 3 and the silane coupling agent 1 at a mass ratio of 100:1 and stir for 2 minutes until they are uniform, and the silicon mass content is 11ppm;

[0087] The synthetic mica powder 1 is a product produced by Suzhou Shenwei, with an average flake diameter of 40 μm; the synthetic mica powder 2 is a product produced by Suzhou Shenwei, with an average flake diameter of 80 μm;

[0088] The synthetic mica powder 3 is a product produced by Suzhou Shenwei, with an average flake diameter of 20 μm;

[0089] The synthetic mica powder 4 is a product produced by Suzhou Shenwei, with an average flake diameter of 50 μm;

[0090] The natural mica powder is HYC-300 produced by Jiangmen Jingda, with an average flake diameter of 30 μm;

[0091] The antioxidant is a mixture of a commercially available hindered phenol antioxidant and a commercially available phosphite antioxidant in a mass ratio of 1:1;

[0092] The lubricant is the commercially available lubricant MSA-255 produced by Guohua Polyfluoride;

[0093] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.

[0094] After reverse testing, the mesh size of talc powder and the average flake diameter of synthetic mica powder in each product basically did not change before and after processing (the change rate of a single product was less than 5%), so it can be considered that the size of talc powder and synthetic mica powder did not change before and after processing. Similarly, the size of silane-modified nanocellulose in the product after modification and processing is almost the same as the diameter and length of the initial nanocellulose material, so it can be considered that the size of the nanocellulose in the product is the same as the initial material.

[0095] Table 1

[0096]

[0097] Table 2

[0098]

[0099]

[0100] In order to verify the performance of the polypropylene composite material of the present invention, the products prepared in each embodiment and comparative example were subjected to the following performance tests, and the specific steps are as follows:

[0101] (1) Solvent swelling resistance test: Each example and comparative example product was injection molded and cut into a sample of 100×100 mm size. 5 mL of organic solvent was dropped on the sample with a dropper, and then placed in a 100°C oven for 240 h. After cooling to room temperature, it was wiped clean with a clean fine cotton cloth. By comparison, it was evaluated whether the position of the sample stained with organic solvent changed. The evaluation level was described as follows. At the same time, it was observed whether there was solvent precipitation on the back, and the precipitation time was recorded. The swelling resistance of the sample was evaluated from two aspects. The organic solvent used in this experiment was engine oil.

[0102] The positive rating criteria are:

[0103] Level 1: The oil stain on the experimental part can be wiped off, the color does not change, gray level 5;

[0104] Level 2: The oil stains on the experimental part can be wiped off, the color changes slightly, and the grayscale is 4 / 5;

[0105] Level 3: The oil stains on the experimental part can be wiped off, the color has obvious changes, and the grayscale is level 4;

[0106] Level 4: The oil stains on the experimental part can be wiped off, the color has a significant change, and the grayscale is 3 / 4;

[0107] Level 5: The oil stains on the experimental part cannot be completely wiped off, most of them have penetrated into the sample, the color has changed greatly, gray level 3;

[0108] Level 6: The oil stains on the experimental parts cannot be wiped off and have basically penetrated into the sample.

[0109] (2) Appearance test: Cut each example and comparative example product into 100×100 mm samples, observe whether there are obvious flow marks on the surface of the samples, and count the pits on the surface. Then grade them. The higher the grade, the worse the appearance.

[0110] The grading standards are:

[0111] Level 1: 0.1mm pitting number <10, no pitting larger than 0.1mm

[0112] Level 2: 0.1mm pit number ≥ 10, 0.2mm pit number < 10, no pit larger than 0.2mm;

[0113] Level 3: 0.2mm pitting number ≥10, 0.3mm pitting number <10, no pitting larger than 0.3mm;

[0114] Level 4: ≥10 pits on the surface of 0.3mm, <10 pits on the surface of 0.4mm, no pits larger than 0.4mm;

[0115] The test results are shown in Tables 3 and 4.

[0116] Table 3

[0117]

[0118]

[0119] Table 4

[0120] Test items Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Comparative Example 9 Positive swelling grade 5 3 4 3 2 3 3 4 3 Back side precipitation time (h) 24 109 153 180 210 162 168 135 153 Are there flow marks? none none none have have have none none none Appearance grade 1 2 1 2 2 3 1 1 1

[0121] It can be seen from Table 3 and Table 4 that, compared with the product of Comparative Example 1 without any modified components, during the solvent swelling resistance test, the front side of the polypropylene composite material of the present invention can still reach level 3 or below after being immersed in an organic solvent for 240 hours, and the precipitation time of the solvent on the back side can reach more than 180 hours. On the other hand, the appearance of the product is good and can be maintained at level 2 or below, and the appearance grade can be maintained at a lower level, with a small number of pits and no obvious flow marks, indicating that the isolation structure formed based on the specific silane-modified nanocellulose and synthetic mica powder can effectively inhibit the swelling erosion of the solvent without significantly affecting the appearance of the product. In the polypropylene composite material of the present invention, it can be known from Examples 1 and 5 to 7 that, in addition to silane-modified nanocellulose and synthetic mica powder, the size of talcum powder as a filler will also have a certain influence on the swelling resistance of the product. When the mesh number of the product is large, as shown in Example 4, the tightness of its filling in the isolation network is low, and the swelling resistance of the product is reduced compared with the products of Examples 1 and 5. The talcum powder in the product of Example 6 is too small in size and is therefore easy to agglomerate, resulting in lower solvent swelling resistance and appearance of the product. In general, the best effect is achieved when the mesh number of talcum powder is 1250 to 3500 mesh. As key components, the sizes of silane-modified nanocellulose and synthetic mica powder will also affect the performance of the product. As shown in Examples 1, 8 to 10, and 11 to 12, when the diameter of the silane-modified nanocellulose in the product is 10 to 30 nm, accounting for more than 95%, the length is 100 to 500 nm, accounting for more than 95%, and the average sheet diameter of the synthetic mica powder is within the range of 30 to 60 μm, the comprehensive performance of the product is the best. On the other hand, when the total amount of the two is constant and the ratio of the two changes, as shown in Examples 1 and 13 to 15, when the mass ratio of the two is maintained within the range of (1:2) to (2:5), the two can exert the best matching effect, and the performance of the formed isolation network structure is the best. In contrast, in the products of Comparative Examples 2 and 3, silane-modified nanocellulose and synthetic mica powder were added separately as modified ingredients, and the swelling resistance of the products was improved compared with that of the product of Comparative Example 1. The effect of using silane-modified nanocellulose alone on improving the solvent precipitation on the back of the product was not ideal, but the front grade was improved to Grade 3; the use of synthetic mica powder alone showed the opposite trend, indicating that the two must be used together to synergistically improve the overall solvent swelling resistance of the product. However, these two should not be added too much, as shown in Comparative Examples 4 and 5. If too much is added, it is easy to cause the isolation network coverage to deteriorate due to the agglomeration effect, and it will also cause the appearance of the product to deteriorate.In addition, it can be seen from Comparative Example 6 that nanocellulose is directly introduced into the polypropylene composite material of the present invention without silane modification, which may have the problem of insufficient compatibility, resulting in the product being unable to form the expected isolation network. At the same time, only at the nanometer size can cellulose be effectively dispersed in the lamellar structure of mica powder to play a role in plugging leaks. If the size is too large, as shown in Comparative Example 7, the performance of the product is poor; as a filler for the lamellar structure, not any modified component can do the job. As shown in Comparative Example 8, a smaller talcum powder is used instead of nanocellulose and modified with synthetic mica powder, and the product's solvent swelling resistance effect is not ideal. As the main material of the isolation structure, it requires higher thermal stability and strength, and the natural mica powder used in Comparative Example 9 does not have the corresponding performance. Therefore, even if the substance also has a lamellar structure, it cannot achieve the desired effect after being used to prepare the polypropylene composite material of the present invention.

[0122] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A polypropylene composite material, characterized in that: The composition comprises the following components in parts by weight: 50-90 parts of polypropylene resin, 3-15 parts of toughening agent, 5-25 parts of talc, 1-2 parts of silane-modified nanocellulose, 2-5 parts of synthetic mica powder and 0.1-2.5 parts of processing aid; The polypropylene resin is copolymer polypropylene, and the melt flow rate of the copolymer polypropylene resin at 230° C. and 2.16 kg load is 1-100 g / 10 min according to ISO 1133-2011; the mesh size of the talc powder is ≥1000 mesh; the diameter of the silane-modified nanocellulose is 2-80 nm, accounting for more than 95%, and the length is 30-2000 nm, accounting for more than 95%; the average flake diameter of the synthetic mica powder is 20-80 μm; the toughening agent is at least one of ethylene / octene copolymer and ethylene / butene copolymer; The silane-modified nanocellulose is obtained by mixing and dispersing nanocellulose and a silane coupling agent; the silane coupling agent comprises at least one of γ-aminopropyl triethoxysilane siloxane, γ-glycidyloxypropyl trimethoxysilane, and γ-methacryloxypropyl siloxane.

2. The polypropylene composite material according to claim 1, characterized in that: The mass ratio of the silane-modified nanocellulose to the synthetic mica powder is (1:2) to (2:5).

3. The polypropylene composite material according to claim 1, characterized in that: The processing aid includes at least one of an antioxidant and a lubricant.

4. The method for preparing the polypropylene composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: After the components are uniformly mixed, they are melt-extruded and granulated in a twin-screw extruder to obtain the polypropylene composite material.

5. Use of the polypropylene composite material according to any one of claims 1 to 3 in the preparation of automotive parts.

Citation Information

Patent Citations

  • Thermoplastic resin composition

    CN103160059A

  • All-natural composite insulating material and preparation method thereof

    CN116622097A

Cited By

  • Modified polypropylene material for annealing-free encapsulation and preparation method thereof

    CN122037440A